Meta-Structure Surface Based on Dielectric Tensor Rotation Induced by AC Electric Field for Insulation Improvement - Shen, Zikui; Hao, YanPeng; Xin, Zhenyu; Wang, Xilin; Jia, Zhidong (Frontiers in Materials, 2022)
Electric field distribution along gas-solid interfaces determines the reliability of insulating components. However, dielectric gradient insulating component prepared by the conventional method is considered to only control the internal electric field, but not beneficial to the surface insulation, especially when the electrode is at an acute angle from the dielectric surface. The aim of this study is to clarify that the meta-structure surface based on dielectric tensor rotation induced by EIA method could improve the surface insulation. The self-assembly and orientation axis rotation of filler particles near the interface was observed by in-situ optical observation, and the relationship between dielectric tensor rotation and electric field refraction was revealed. Simulation of meta-structure surface induced by the EIA method on the basin insulator was conducted. The meta-structure surface exhibits negative and high reduced-permittivity, confining electric field path and transferring the electrical stress from gas to insulator, which offers theoretical support to optimize the surface electric field. Flashover tests on the basin insulator proved the insulation improvement by meta-structure surface.